Multi-gradient aperture activated carbon composite material and preparation method and application thereof

Through physical blending, the formation of activated carbon composite materials with multi-gradient pore sizes has solved the shortcomings of existing activated carbon materials in adsorption performance, service life and environmental treatment, and achieved efficient and economical adsorption effects and suitable for large-scale production.

CN119524804APending Publication Date: 2025-02-28XIAN UNVERSITY OF ARTS & SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510088545.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing activated carbon materials have shortcomings in adsorption performance, service life and environmental treatment, and the uneven pore size distribution affects the adsorption effect.

Method used

By physically blending coal-based activated carbon and wood-based activated carbon, a composite material with multi-gradient pore size is formed, the process route is simplified, the cost is reduced, and it is suitable for large-scale production.

Benefits of technology

It improves the adsorption efficiency and pore utilization rate of activated carbon composite materials, extends the service life, reduces production and use costs, and solves the problem of uneven pore size distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524804A_ABST
    Figure CN119524804A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-gradient aperture activated carbon composite material as well as a preparation method and application thereof, and belongs to the technical field of composite materials. The multi-gradient aperture activated carbon composite material provided by the invention is a coal / wood activated carbon composite material or a coal activated carbon / wood activated carbon / expanded graphite composite material; the coal / wood activated carbon composite material is prepared by physically blending the following components in percentage by mass: 10-98% of coal activated carbon and the balance of wood activated carbon, totaling 100%. The coal-based activated carbon / wood-based activated carbon / expanded graphite composite material is obtained by physically blending the following components in percentage by mass: 85-95% of coal-based / wood-based activated carbon composite material and the balance of expanded graphite, totaling 100%. The multi-gradient aperture activated carbon composite material with considerable economic benefits is obtained from carbon materials with different aperture sizes through a simple physical blending method, and the method is simple to operate, low in cost and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and more specifically to a multi-gradient pore size activated carbon composite material and a preparation method and application thereof. Background Art

[0002] Activated carbon is a porous material with strong adsorption capacity. Its microporous structure is rich and diverse, providing a wide space for the adsorption of various harmful substances. Secondly, the raw materials for the production of activated carbon are mostly natural substances, such as wood, coal, etc., which are non-toxic and harmless and will not pollute the human body and the environment. In addition, activated carbon will not produce secondary pollution during use, so it has significant environmental advantages.

[0003] The adsorption performance of activated carbon is limited and cannot completely adsorb all pollutants. In addition, activated carbon may not have efficient adsorption capacity for certain specific pollutants, which will also limit its effect in practical applications. Secondly, the service life of activated carbon is relatively short. Due to the limited adsorption capacity of activated carbon, once it reaches saturation, its adsorption effect will be greatly reduced. In addition, the disposal of discarded activated carbon is also a problem. Activated carbon will adsorb a large amount of pollutants during the adsorption process, so discarded activated carbon cannot be directly discharged into the environment. If not properly handled, discarded activated carbon may cause secondary pollution to the environment. Finally, the uneven pore size distribution of activated carbon is also a problem. The pore size of activated carbon has an important influence on its adsorption performance. Activated carbon with different pore sizes has different adsorption capacities for molecules of different sizes. However, the pore size distribution inside activated carbon is often uneven, which may result in too many or too few pore sizes, thus affecting its overall adsorption effect.

[0004] Activated carbon has become an excellent adsorbent because of its rich pore structure and huge specific surface area. The adsorption performance of activated carbon is mainly provided by the pore size. In the adsorption process, the pore size of activated carbon is usually divided into three structures according to the size of the pore size, namely macropore, mesopore and micropore. The pore size of macropore is greater than 50nm, the pore size of mesopore is 2nm~50nm, and the pore size of micropore is less than 2nm. The adsorption of activated carbon is mainly caused by the joint action of various pore sizes, and pores of different sizes have different adsorption mechanisms. For most adsorbents, macropores have no adsorption capacity and generally only play a channel role in the adsorption process; mesopores can be used as adsorption sites for large molecules and channels for small molecules; micropores are where most small molecule adsorbents are attached, and the development of micropores is the key to determining the adsorption capacity of activated carbon. According to the different application fields of activated carbon, the pore size distribution of activated carbon needs to be regulated. The commonly used methods of pore size regulation are chemical activation, template method and catalytic pore size regulation. The chemical activation method is to physically mix chemicals and activated carbon evenly, react with carbon-based materials under high temperature conditions, and form a rich microporous structure through a series of cross-linking polycondensation reactions. The existing technology uses hemp cloth as raw material and uses phosphoric acid activation to prepare activated carbon fibers. The pore size distribution test of the sample found that after phosphoric acid activation, the pore size is mainly micropores, with both ultra-micropores and ultra-micropores, only a small number of mesopores, and basically no macropores. The template method is a molding method that adds polymers to inorganic molding. Porous carbon with the same inorganic template can be obtained by carbonization. The existing technology uses coal tar as raw material and uses nano-silica template method to prepare mesoporous activated carbon. The catalytic pore size regulation method can effectively promote the performance improvement of mesoporous materials in catalytic activation reactions. These reactions need to be optimized in the area around metal particles. Non-catalytic activation reactions mainly produce micropores. The existing technology uses chemical catalysis to prepare metal activated carbons of different types and quantities. Metal catalysis is conducive to the increase of activated carbon pore size, and the increase of micropores and mesopores is particularly obvious. However, when the pore size of materials is controlled according to existing methods, the process route is long, the large-scale production process is complex, the production and use costs are high, and it is not suitable for large-scale application. Summary of the invention

[0005] In view of the above problems, the present invention provides a multi-gradient pore size activated carbon composite material and a preparation method and application thereof. Carbon materials with different pore sizes are blended by a simple physical blending method to obtain a multi-gradient pore size activated carbon composite material with considerable economic benefits. The multi-gradient pore size activated carbon composite material is simple to operate, low in cost, and suitable for large-scale production.

[0006] The first object of the present invention is to provide a multi-gradient pore size activated carbon composite material, which is a coal / wood activated carbon composite material or a coal activated carbon / wood activated carbon / expanded graphite composite material.

[0007] The coal-based / wood-based activated carbon composite material is obtained by physically blending the following components in percentage by mass: 10% to 98% coal-based activated carbon and the rest wood-based activated carbon, which together amount to 100%; the coal-based activated carbon and the wood-based activated carbon are physically blended to form a composite pore structure with a gradient distribution of small pores and medium pores; for example, the mass percentage of the coal-based activated carbon is 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 98%, etc., and the corresponding mass percentage of the wood-based activated carbon is 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10%, 2%, etc.

[0008] The coal-based activated carbon / wood-based activated carbon / expanded graphite composite material is obtained by physically blending the following components in percentage by mass: 85% to 95% of the coal-based / wood-based activated carbon composite material, and the rest is expanded graphite, which is 100% in total; in the coal-based / wood-based activated carbon composite material, the coal-based activated carbon, the wood-based activated carbon and the expanded graphite are physically blended to form a composite pore structure with a gradient distribution of small pores, medium pores and large pores. For example, the mass percentage of the coal-based / wood-based activated carbon composite material is 85%, 90%, 95%, etc., and the corresponding mass percentage of the expanded graphite is 15%, 10%, 5%, etc., but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0009] In a preferred embodiment of the present invention, the coal-based / wood activated carbon composite material is obtained by physically blending the following components in mass percentage: 30% to 60% coal-based activated carbon, and the rest is wood activated carbon, which totals 100%. For example, the mass percentage of coal-based activated carbon is 30%, 40%, 50%, 60%, etc., and the corresponding mass percentage of wood activated carbon is 70%, 60%, 50%, 40%, etc., but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0010] In a preferred embodiment of the present invention, the coal-based / wood-based activated carbon composite material is obtained by physically blending the following components in percentage by mass: 30% coal-based activated carbon and 70% wood-based activated carbon.

[0011] In a preferred embodiment of the present invention, the coal-based / wood activated carbon composite material is obtained by physically blending the following components in percentage by mass: 60% coal-based activated carbon and 40% wood activated carbon.

[0012] In a preferred embodiment of the present invention, the multi-gradient pore size activated carbon composite material also includes expanded graphite, and the multi-gradient pore size activated carbon composite material is obtained by physically blending the following components in mass percentage: 85% to 90% of the coal / wood activated carbon composite material, and the rest is expanded graphite, which totals 100%. For example, the mass percentage of the coal / wood activated carbon composite material is 85%, 86%, 87%, 88%, 89%, 90%, etc., and the corresponding mass percentage of expanded graphite is 15%, 14%, 13%, 12%, 11%, 10%, etc., but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0013] In a preferred embodiment of the present invention, the multi-gradient pore size activated carbon composite material is obtained by physically blending the following components in percentage by mass: 85% coal / wood activated carbon composite material and 15% expanded graphite.

[0014] The second object of the present invention is to provide a method for preparing the above-mentioned multi-gradient pore size activated carbon composite material, the preparation method comprising: physically blending coal-based activated carbon and wood-based activated carbon until uniform and then drying to obtain a coal-based / wood-based activated carbon composite material.

[0015] Or the coal-based activated carbon and wood-based activated carbon are physically blended until uniform and then dried to obtain a coal-based / wood-based activated carbon composite material; the coal-based / wood-based activated carbon composite material and expanded graphite are physically blended until uniform and then dried to obtain a coal-based activated carbon / wood-based activated carbon / expanded graphite composite material.

[0016] The third object of the present invention is to provide an application of the above-mentioned activated carbon composite material in the preparation of a material suitable for adsorbing adsorbents with a size less than 2nm, and the multi-gradient pore size activated carbon composite material is a coal / wood activated carbon composite material.

[0017] The fourth object of the present invention is to provide an application of the above-mentioned activated carbon composite material in the preparation of a material suitable for adsorbing adsorbents with an adsorption size of 2nm~50nm, wherein the multi-gradient pore size activated carbon composite material is a coal / wood activated carbon composite material or a coal activated carbon / wood activated carbon / expanded graphite composite material.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The present invention can form a composite material with gradient pore size by simply physically blending coal-based activated carbon, wood-based activated carbon and expanded graphite. Compared with the prior art, the present invention does not need to modify the activated carbon under high temperature conditions, and can be physically blended at room temperature. The operation process is simple, the operability is strong, and the actual effect is obvious. The multi-gradient pore size activated carbon composite material prepared by the present invention has a wide adjustable range of pore size, and the adjustable range can be customized and regulated according to the use requirements; the prepared activated carbon composite material eliminates the bottleneck problem of the adsorbate entering the activated carbon material with a single pore. Compared with the single activated carbon, the present invention improves the adsorption efficiency of the activated carbon composite material and the utilization rate of the pores, and reduces the use cost. The present invention physically blends coal-based activated carbon and wood-based activated carbon, or physically blends coal-based activated carbon, wood-based activated carbon and expanded graphite. The pore size distribution of the composite material can be regulated by the physical blending method, and its adsorption performance can be improved, which can be used to adsorb different pollutants. The multi-gradient pore size activated carbon composite material prepared by the present invention has a short preparation process route, simple operation, low cost, great economic benefit potential, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 are scanning electron microscope images of C-AC, W-AC and EG, wherein A1 is the scanning electron microscope image of C-AC with a scale of 10 μm, A2 is the scanning electron microscope image of C-AC with a scale of 2 μm, B1 is the scanning electron microscope image of W-AC with a scale of 10 μm, B2 is the scanning electron microscope image of W-AC with a scale of 2 μm, C1 is the scanning electron microscope image of EG with a scale of 10 μm, and C2 is the scanning electron microscope image of EG with a scale of 2 μm.

[0020] Figure 2 Pore ​​size distribution diagram of different materials, where A is C-AC, B is W-AC, C is EG, D is C-AC-60% / W-AC-40%, E is C-AC-30% / W-AC-70%, and F is CW85% / EG15%.

[0021] Figure 3 This is a comparison chart between the measured values ​​and theoretically calculated values ​​of iodine adsorption values ​​of different composite materials.

[0022] Figure 4 This is a trend chart of the synergistic effect of iodine adsorption values ​​of different composite materials.

[0023] Figure 5 This is a comparison chart of the measured values ​​and theoretically calculated values ​​of methylene blue adsorption values ​​of different composite materials.

[0024] Figure 6 The synergistic effect trend of methylene blue adsorption values ​​of different composite materials.

[0025] Figure 7This is a graph showing the changes in the synergistic price added value and synergistic price increment ratio for different composite materials. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Funnel effect mechanism: When adsorbing small molecules with a size less than 2nm, the adsorbent material with well-developed small pores has a bottleneck problem in the process of adsorbing small molecules with a size less than 2nm due to its relatively small pore size, which affects the adsorption efficiency of the adsorbent material and the effective utilization of the internal pores of the material. The adsorbent material with well-developed medium pore size is physically blended into it, and the small pores and medium pores in the composite material are matched with each other to form a composite pore structure with a gradient distribution. When adsorbing small molecules, the medium pores in the composite material will form a funnel at the small pores, eliminating the bottleneck of small molecules entering the pores of small pore materials. The small molecules can smoothly enter the pores of the composite material, thereby improving the overall adsorption efficiency of the composite material and the effective utilization of the internal pores of the composite material. ; When adsorbing macromolecular adsorbates with a size of 2nm~50nm, the adsorbent material with developed mesopores has a relatively small pore size, and there is a bottleneck problem for the macromolecular adsorbates to enter the pores, which affects the adsorption efficiency of the adsorbent material and the effective utilization of the pores inside the material. The adsorbent material with developed macropores is physically blended into it, and the mesopores and macropores in the composite material are matched with each other to form a composite pore structure with a gradient distribution. When adsorbing macromolecular adsorbates, the macropores in the composite material will form a funnel at the mesopores, eliminating the bottleneck for the macromolecular adsorbates to enter the pores of the mesoporous material. The macromolecular adsorbates can smoothly enter the pores of the composite material, thereby improving the overall adsorption efficiency of the composite material and the effective utilization of the internal pores of the composite material. It should be noted that when materials with different pore sizes are compounded according to the method of the present invention, the pore size gradient configuration of the materials needs to be considered. Taking the raw materials used in the present invention as an example, assuming that the two raw materials, coal-based activated carbon and commercially available expanded graphite, are physically blended, relative to the coal-based activated carbon with well-developed small pores, the commercially available expanded graphite with well-developed large pores has a narrow pore range, and lacks the wood activated carbon with well-developed medium pores in the middle. It is impossible to form a composite structure with a gradient configuration of small pores, medium pores and large pores, and it is impossible to effectively form a funnel effect, resulting in poor adsorption effect.

[0028] The graphite oxide used in the present invention is prepared from coal-based graphite from the washing center of Ningxia Coal Industry Co., Ltd. of the State Energy Group, with reference to Section 1.2 of "Preparation and Electrochemical Performance of Coal-based Graphene" published by Zhao Chunbao et al. in "Chemical Engineer" No. 10, 2017. The preparation method of the expanded graphite used in the present invention is: add the graphite oxide to the crucible, heat expand in a muffle furnace at 630°C in an air atmosphere for about 15 seconds, and when a bang is heard, take out the crucible immediately to obtain expanded graphite, which is recorded as EG. The wood activated carbon used in the present invention was purchased from Pingdingshan Green Origin Activated Carbon Co., Ltd., marked as W-AC, and the coal-based activated carbon was purchased from Pingdingshan Green Origin Activated Carbon Co., Ltd., marked as C-AC.

[0029] Example 1 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is a coal / wood activated carbon composite material. The coal / wood activated carbon composite material is composed of the following components in the following mass percentages: 10% coal activated carbon and 90% wood activated carbon.

[0030] 0.1g of C-AC and 0.9g of W-AC were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours to successfully prepare a coal-based / wood activated carbon composite material, recorded as C-AC-10% / W-AC-90%.

[0031] Example 2 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is a coal / wood activated carbon composite material. The coal / wood activated carbon composite material is composed of the following components in mass percentage: 20% coal activated carbon and 80% wood activated carbon.

[0032] 0.2 g of C-AC and 0.8 g of W-AC were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours to successfully prepare a coal-based / wood activated carbon composite material, recorded as C-AC-20% / W-AC-80%.

[0033] Example 3 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is a coal / wood activated carbon composite material. The coal / wood activated carbon composite material is composed of the following components in the following mass percentages: 30% coal activated carbon and 70% wood activated carbon.

[0034] 0.3 g of C-AC and 0.7 g of W-AC were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours to successfully prepare a coal-based / wood activated carbon composite material, recorded as C-AC-30% / W-AC-70%.

[0035] Example 4 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is a coal / wood activated carbon composite material. The coal / wood activated carbon composite material is composed of the following components in the following mass percentages: 40% coal activated carbon and 60% wood activated carbon.

[0036] 0.4 g of C-AC and 0.6 g of W-AC were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours to successfully prepare a coal-based / wood activated carbon composite material, recorded as C-AC-40% / W-AC-60%.

[0037] Example 5 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is a coal / wood activated carbon composite material. The coal / wood activated carbon composite material is composed of the following components in mass percentage: 50% coal activated carbon and 50% wood activated carbon.

[0038] 0.5 g of C-AC and 0.5 g of W-AC were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours to successfully prepare a coal-based / wood activated carbon composite material, which was recorded as C-AC-50% / W-AC-50%.

[0039] Example 6 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is a coal / wood activated carbon composite material. The coal / wood activated carbon composite material is composed of the following components in the following mass percentages: 60% coal activated carbon and 40% wood activated carbon.

[0040] 1.8001g of C-AC and 1.1998g of W-AC were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours. A coal-based / wood activated carbon composite material with a mass of 2.9999g was successfully prepared, recorded as C-AC-60% / W-AC-40%.

[0041] Example 7 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is a coal / wood activated carbon composite material. The coal / wood activated carbon composite material is composed of the following components in mass percentage: 70% coal activated carbon and 30% wood activated carbon.

[0042] 0.7 g of C-AC and 0.3 g of W-AC were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours to successfully prepare a coal-based / wood activated carbon composite material, recorded as C-AC-70% / W-AC-30%.

[0043] Example 8 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is a coal / wood activated carbon composite material. The coal / wood activated carbon composite material is composed of the following components in the following mass percentages: 80% coal activated carbon and 20% wood activated carbon.

[0044] 0.8 g of C-AC and 0.2 g of W-AC were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours to successfully prepare a coal-based / wood-based activated carbon composite material, which was recorded as C-AC-80% / W-AC-20%.

[0045] Example 9 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is a coal / wood activated carbon composite material. The coal / wood activated carbon composite material is composed of the following components in mass percentage: 90% coal activated carbon and 10% wood activated carbon.

[0046] 0.9 g of C-AC and 0.1 g of W-AC were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours to successfully prepare a coal-based / wood activated carbon composite material, which was recorded as C-AC-90% / W-AC-10%.

[0047] Example 10 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is composed of the following components in percentage by mass: 85% of the coal / wood activated carbon composite material prepared in Example 6 and 15% of expanded graphite.

[0048] 0.8502g of C-AC-60% / W-AC-40% composite material and 0.1508g of EG were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours. A coal-based activated carbon / wood-based activated carbon / expanded graphite composite material with a mass of 1.001g was successfully prepared, recorded as CW85% / EG15%.

[0049] Embodiment 11 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is composed of the following components in percentage by mass: 90% of the coal / wood activated carbon composite material prepared in Example 6 and 10% of expanded graphite.

[0050] 0.9g of C-AC-60% / W-AC-40% composite material and 0.1g of EG were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours. The coal-based activated carbon / wood-based activated carbon / expanded graphite composite material was successfully prepared, recorded as CW90% / EG10%.

[0051] Example 12 The present embodiment provides a multi-gradient pore size activated carbon composite material, which is composed of the following components in percentage by mass: 95% of the coal / wood activated carbon composite material prepared in Example 6 and 5% of expanded graphite.

[0052] 0.95 g of C-AC-60% / W-AC-40% composite material and 0.05 g of EG were placed in a mortar. The grinding and blending operation was continued for 1 hour to ensure that the two were fully physically blended. After the grinding and blending was completed, the resulting blend was placed in an oven at 120°C and dried for 2 hours to prepare a coal-based activated carbon / wood-based activated carbon / expanded graphite composite material, marked as CW95% / EG5%.

[0053] The following is a performance test of the materials prepared in the examples. The iodine adsorption value was determined according to the provisions of the national standard GB / T12496.8-2015 "Determination of iodine adsorption value of coal-based granular activated carbon experimental method", and the iodine adsorption value was determined for different materials. This determination method is mainly used to objectively evaluate the degree of development of the small pores of activated carbon and the ability to adsorb small molecular adsorbates. The methylene blue adsorption value was determined according to the relevant provisions of the national standard GB / T 7702.6-2015 "Determination of methylene blue adsorption value of coal-based granular activated carbon experimental method", and the methylene blue adsorption value was determined for different materials. This determination method is mainly used to objectively evaluate the degree of development of the pores in activated carbon and the ability to adsorb large molecular adsorbates.

[0054] Figure 1 A1 and A2 in the figure are scanning electron microscope images of C-AC at 5,000 times and 20,000 times magnification respectively. Figure 1 From A1 in the figure, it can be seen that C-AC presents a block structure of different sizes, and its surface and internal holes cannot be clearly seen. Figure 1 A small amount of holes can be seen in C-AC in A2, indicating that C-AC is mainly composed of medium and small pores at the microscopic level. Figure 1 B1 and B2 in the figure are scanning electron microscope images of W-AC at 5,000 times and 20,000 times magnification respectively. Figure 1 From B1 and B2 in the figure, it can be seen that W-AC presents a smaller and more uniform block structure. Compared with C-AC, more pore structures can be obviously observed on its surface, indicating that the pore size distribution of W-AC is wider than that of C-AC, but it is still dominated by medium and small pores. Figure 1 C1 and C2 in the figure are scanning electron microscope images of EG at 5,000 times and 20,000 times magnification respectively. Figure 1 From C1 in the figure, it can be clearly seen that the appearance of EG is worm-like. Figure 1 In C2, abundant pores of different sizes can be clearly observed, indicating that EG has abundant macroporous structures.

[0055] Figure 2 The pore size distribution diagrams of the samples prepared by C-AC, W-AC, EG, Example 6, Example 3 and Example 10, respectively, Figure 2 Combining A and B in Table 1, we can see that the pore structures of C-AC and W-AC are distributed in the range of 2nm~220nm, and they decrease in sequence, with the main pore size concentrated below 50nm; compared with C-AC, in the range of 2nm~50nm, W-AC has a larger proportion of large-size pore structures. This shows that C-AC and W-AC are generally dominated by medium and small pores, and W-AC has more large-size pore structures. Compared with C-AC and W-AC, Figure 2As shown in Figure C, the pore size distribution of EG is more uniform in the range of 2nm~220nm, the pore size of 2nm~5nm accounts for a smaller proportion, and the pore size greater than 50nm accounts for more than 17%, which indicates that EG has rich mesoporous and macroporous structures. Figure 2 D and E in the figure show that the samples prepared in Example 6 and the samples prepared in Example 3 are mainly composed of small-sized mesopore structures of 2nm~5nm, but as the W-AC ratio increases, the large-sized mesopore structures of 5nm~50nm in the two composite materials are more abundant, forming a more optimal hierarchical configuration of small-sized mesopores and large-sized mesopores. Figure 2 F in the graph shows that the sample prepared in Example 10 is also mainly composed of small-sized mesopore structures of 2nm~5nm, but the addition of EG with rich mesopore and macropore structures significantly increases the proportion of mesopore and macropore structures, and presents the characteristics of mesopore and macropore gradient configuration. The better pore structure gradient configuration makes it easier for the three composite materials to form a funnel effect at the microscopic level, which is beneficial to the improvement of their adsorption performance. This also proves that the distribution of the microscopic pore size of the composite material can be regulated by compounding materials with different pore sizes.

[0056] Table 1 Pore size ratio of different materials

[0057] Figure 3 Curve A and curve B are the measured iodine adsorption value and theoretical iodine adsorption value of the coal / wood activated carbon composite material, respectively. Figure 3 It can be found that with the gradual increase in the amount of W-AC added, the measured iodine adsorption value of the composite material shows a continuous growth trend. And in the entire addition process, the measured value always remains above the theoretical value, indicating that the addition of W-AC can effectively improve the iodine adsorption energy of the composite material and improve the ability of the composite material to adsorb small molecular adsorbents.

[0058] Figure 4 The synergistic effect trend diagram of the composite material is shown in Table 2. When the addition amount of W-AC reaches 40%, the synergistic effect of C-AC-60% / W-AC-40% reaches the maximum, and the measured iodine adsorption value is as high as 804 mg / g. The synergistic effect value is 30 mg / g, which is 3.88% higher than the theoretical iodine adsorption value of 774 mg / g, and 30.3% higher than the iodine adsorption value of pure C-AC of 617 mg / g. This is because the addition of W-AC with a larger pore size changes the pore size distribution of the composite material, forming a funnel effect, accelerating the adsorption rate and increasing the actual utilization rate of the C-AC pores, enhancing the iodine adsorption performance of the composite material, and improving the ability of the composite material to adsorb small molecular adsorbates.

[0059] Table 2 Analysis of iodine adsorption values ​​of composite materials

[0060] Figure 5 Curve A in the middle is the measured adsorption value of methylene blue of the coal / wood activated carbon composite material. Curve B is the theoretical adsorption value of methylene blue of the coal / wood activated carbon composite material. By observing curve A, it can be found that with the gradual increase in the amount of W-AC added, the measured adsorption value of methylene blue of the coal / wood activated carbon composite material shows a continuous growth trend. And during the entire addition process, curve A always remains above curve B. This phenomenon fully demonstrates that the addition of W-AC can effectively improve the methylene blue adsorption capacity of the coal / wood activated carbon composite material and improve the ability of the composite material to adsorb large molecular adsorbates.

[0061] Figure 6 The trend diagram of the synergistic effect of coal / wood activated carbon composite materials shows a bimodal diagram. In combination with Table 3, it can be seen that when the addition amount of W-AC reaches 70%, the synergistic effect of the coal / wood activated carbon composite material reaches the maximum, and the measured methylene blue adsorption value of C-AC-30% / W-AC-70% is 190.72 mg / g. The synergistic effect value is 15.6 mg / g, which is 8.9% higher than its theoretical value of methylene blue, and 103% higher than the pure C-AC methylene blue adsorption value of 93.87 mg / g. When the addition amount of W-AC reaches 5%, the measured methylene blue adsorption value of C-AC-95% / W-AC-5% is 108.55 mg / g. The synergistic effect value is 8.9 mg / g, which is 8.9% higher than its theoretical value of methylene blue, and 15.64% higher than the pure C-AC methylene blue adsorption value of 93.87 mg / g. This is because the proportion of pore size below 50 nm in W-AC is larger than that in C-AC, while the proportion of pore size above 50 nm in C-AC is larger, which makes W-AC and C-AC funnel each other, resulting in a double funnel effect, which accelerates the adsorption rate and improves the actual utilization rate of the activated carbon composite material, enhances its methylene blue adsorption performance, and improves the ability of the composite material to adsorb large molecular adsorbates.

[0062] Table 3 Analysis of the adsorption value of methylene blue for composite materials

[0063] Table 4 is a comparison table of the iodine adsorption value and methylene blue adsorption value of the coal-based / wood activated carbon composite material. It can be seen from Table 4 that when the addition amount of W-AC reaches 40%, the composition of the coal-based / wood activated carbon composite material is C-AC-60% / W-AC-40%, and the actual measured iodine adsorption value is as high as 804 mg / g. Compared with the theoretical iodine adsorption value of 774 mg / g, it is increased by 3.88%.

[0064] When the addition amount of W-AC reaches 70%, the composition of the coal / wood activated carbon composite material is C-AC-30% / W-AC-70%, and the measured methylene blue adsorption value is 190.7 mg / g, which is 8.9% higher than the theoretical value of methylene blue. The optimal ratio of the optimal value of methylene blue adsorption and the optimal value of iodine adsorption of the coal / wood activated carbon composite material is different.

[0065] From the results in Table 4, it can be seen that due to the different molecular sizes of methylene blue and iodine, the requirements for the microscopic size of the adsorption material are also different. The microscopic size and pore size distribution of C-AC-60% / W-AC-40% are more conducive to the adsorption of small molecular adsorbates such as iodine, while the microscopic size and pore size distribution of C-AC-30% / W-AC-70% are more conducive to the adsorption of large molecular adsorbates such as methylene blue.

[0066] Table 4 Comparison of adsorption performance of different composite materials

[0067] From Table 5, it can be seen that the composite material has the lowest reduction in the synergistic effect of iodine adsorption value improvement rate, and the CW85% / EG5% has a reduction of 0.3%. The measured iodine adsorption value is 750.3 mg / g, and the theoretical iodine adsorption value is 752.5 mg / g. There is no synergistic effect of 1+1>2. This is mainly because EG is rich in mesopores and macropores, and its own iodine adsorption value is low, which lowers the iodine adsorption value of the composite material.

[0068] In addition, the iodine molecule is small in size, and it is easy to desorb after being adsorbed in the mesopores and macropores of the composite material, and the funnel effect cannot be formed. This also proves that the composition of the wood activated carbon, coal-based activated carbon and expanded graphite in the activated carbon composite material can be adjusted according to the method of the present invention to adsorb large-sized adsorbates or small-sized adsorbates.

[0069] Table 5 Analysis of iodine adsorption values ​​of different composite materials

[0070] The data in Table 6 show that the synergistic effect of the activated carbon composite material with the highest methylene blue adsorption value improvement is CW85% / EG15%, and the measured methylene blue adsorption value reaches 155.0 mg / g, which is 16.8% higher than the theoretical methylene blue adsorption value of 132.6 mg / g of the activated carbon composite material.

[0071] Depend on Figure 2From Figure F in the figure combined with the pore size distribution of CW85% / EG15%, it can be seen that this is mainly because EG is rich in macropores. The pore size of CW85% / EG15% forms a composite pore structure with a gradient configuration of small pores, medium pores and large pores. When adsorbing methylene blue with larger molecular size, it is easier to produce a funnel effect, which accelerates the adsorption rate of methylene blue and the actual utilization rate of the pores of the activated carbon composite material, and improves the adsorption value of methylene blue of the activated carbon composite material.

[0072] Table 6 Analysis of methylene blue adsorption values ​​of different composite materials

[0073] When preparing the activated carbon composite material, the present invention only needs to physically blend the raw materials evenly before use, and no other operations are required, and the preparation method is simple. The present invention conducted a survey on the prices of commercially available activated carbon, as shown in Tables 7 to 9.

[0074] According to current market research prices, for every 100 mg / g iodine value, the price of activated carbon is about 1,000 yuan / ton; for every 1 mg / g methylene blue value, the price of activated carbon is about 35 yuan / ton; the price of activated carbon composite materials is calculated according to the above price change rules.

[0075] The survey results are shown in Table 7. According to the above price change rules, the iodine adsorption value of the C-AC-60% / W-AC-40% composite material is 804.5 mg / g, and the calculated price is 8045 yuan / ton, which is 304 yuan higher than the theoretical iodine adsorption value of 1+1=2, which is 7741 yuan / ton. This is mainly due to the extra profit brought by the synergistic effect of 1+1>2.

[0076] As shown in Table 8, the methylene blue adsorption value obtained by the C-AC-30% / W-AC-70% test is 190.7 mg / g, and the calculated price is 6675 yuan / ton. Compared with the theoretical methylene blue adsorption value of 1+1=2, the calculated price is 6129 yuan / ton, which is 546 yuan higher per ton, which is a considerable economic benefit. This is mainly due to the extra profit brought by the synergistic effect of 1+1>2.

[0077] As shown in Table 9, the methylene blue adsorption value obtained by CW85% / EG15% test is 155.0 mg / g, and the calculated price is 5425 yuan / ton. Compared with the calculated price of 4641 yuan / ton of the theoretical methylene blue adsorption value of 1+1=2, the economic benefit is increased by 784 yuan per ton, which is mainly due to the extra profit brought by the synergistic effect of 1+1>2.

[0078] Table 7 Analysis of the price corresponding to the iodine adsorption value of coal / wood activated carbon composite materials

[0079] Table 8 Analysis of the price corresponding to the methylene blue adsorption value of coal / wood activated carbon composite materials

[0080] Table 9 Analysis of the price calculation of the methylene blue adsorption value of coal-based activated carbon / wood-based activated carbon / expanded graphite composite materials

[0081] Figure 7 The figure is the relationship between the synergistic price value-added amount and the synergistic price increment ratio and the amount of wood activated carbon added. Curve A is the synergistic price value-added, and curve B is the synergistic price increment ratio.

[0082] Synergistic value added = (synergistic effect value / 100) * iodine adsorption value price change. Synergistic price increment ratio = synergistic price added / composite material theoretical price. The synergistic price increment ratio can intuitively prove the additional profit created by the synergistic effect in the product.

[0083] Depend on Figure 7 From the curves A and B in the figure, it can be seen that in the coal-based / wood activated carbon composite material, as the amount of W-AC added continues to increase, the synergistic price value-added and synergistic price increment ratio of the coal-based / wood activated carbon composite material first increase and then decrease, and the maximum values ​​of the two curves are at different W-AC addition amounts. Among them, when the amount of W-AC added is 60%, the synergistic price increment ratio of the coal-based / wood activated carbon composite material reaches the maximum value of 7.3%, that is, through the combination of the two activated carbons, the product profit can be increased by up to 7.3% per ton of product.

[0084] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0085] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A multi-gradient pore size activated carbon composite material, characterized in that: The multi-gradient pore size activated carbon composite material is a coal-based / wood-based activated carbon composite material or a coal-based activated carbon / wood-based activated carbon / expanded graphite composite material; The coal-based / wood-based activated carbon composite material is obtained by physically blending the following components in percentage by mass: 10% to 98% coal-based activated carbon and the rest wood-based activated carbon, which together amount to 100%; the coal-based activated carbon and wood-based activated carbon are physically blended to form a composite pore structure with a gradient distribution of small pores and medium pores; The coal-based activated carbon / wood-based activated carbon / expanded graphite composite material is obtained by physically blending the following components in percentage by mass: 85% to 95% of the coal-based / wood-based activated carbon composite material, and the rest is expanded graphite, which totals 100%; in the coal-based / wood-based activated carbon composite material, the coal-based activated carbon, wood-based activated carbon and expanded graphite are physically blended to form a composite pore structure with a gradient distribution of small pores, medium pores and large pores.

2. The multi-gradient pore size activated carbon composite material according to claim 1, characterized in that: The coal-based / wood-based activated carbon composite material is obtained by physically blending the following components in percentage by mass: 30% to 60% of coal-based activated carbon and the rest of wood-based activated carbon, which is 100% in total.

3. The multi-gradient pore size activated carbon composite material according to claim 2, characterized in that: The coal-based / wood-based activated carbon composite material is obtained by physically blending the following components in percentage by mass: 30% coal-based activated carbon and 70% wood-based activated carbon.

4. The multi-gradient pore size activated carbon composite material according to claim 2, characterized in that: The coal-based / wood-based activated carbon composite material is obtained by physically blending the following components in percentage by mass: 60% coal-based activated carbon and 40% wood-based activated carbon.

5. The multi-gradient pore size activated carbon composite material according to claim 4, characterized in that: The coal-based activated carbon / wood-based activated carbon / expanded graphite composite material is obtained by physically blending the following components in percentage by mass: 85% to 90% of the coal-based / wood-based activated carbon composite material and the rest of the expanded graphite, which is 100% in total.

6. The multi-gradient pore size activated carbon composite material according to claim 5, characterized in that: The coal-based activated carbon / wood-based activated carbon / expanded graphite composite material is obtained by physically blending the following components in percentage by mass: 85% of the coal-based / wood-based activated carbon composite material and 15% of the expanded graphite.

7. A method for preparing the multi-gradient pore size activated carbon composite material according to any one of claims 1 to 6, characterized in that: The preparation method comprises: physically blending coal-based activated carbon and wood-based activated carbon until uniform and then drying to obtain a coal-based / wood-based activated carbon composite material; Or the coal-based activated carbon and wood-based activated carbon are physically blended until uniform and then dried to obtain a coal-based / wood-based activated carbon composite material; the coal-based / wood-based activated carbon composite material and expanded graphite are physically blended until uniform and then dried to obtain a coal-based activated carbon / wood-based activated carbon / expanded graphite composite material.

8. Use of the multi-gradient pore size activated carbon composite material according to claim 1 in preparing a material for adsorbing an adsorbent with an adsorption size of less than 2 nm, characterized in that: The multi-gradient pore size activated carbon composite material is a coal / wood activated carbon composite material.

9. Use of the multi-gradient pore size activated carbon composite material according to claim 1 in preparing a material for adsorbents with an adsorption size of 2nm to 50nm, characterized in that: The multi-gradient pore size activated carbon composite material is a coal-based / wood-based activated carbon composite material or a coal-based activated carbon / wood-based activated carbon / expanded graphite composite material.

Citation Information

Patent Citations

  • Expanded graphite-based composite material and preparation method thereof

    CN101439280A

  • Bamboo-based macroporous biological activated carbon and preparation method thereof

    CN104692378A

  • Activated carbon with high microporosity and high specific surface area and preparation method thereof

    CN114132925A

  • Hierarchical porous activated carbon and preparation method thereof

    CN116062753A

  • Composite material comprising activated carbon and expanded graphite

    US20030003289A1